Anti-hyperglycemic Effect of Stephania Glabra Tubers in Alloxan Induced Diabetic Mice (Journal of Medicine, 2010)
Different doses of ethanolic extract of Stephania glabra tuber were evaluated for antihyperglycemic activity in alloxan induced diabetic mice. The oral administration of 100, 200 and 500 mg/kg body weight showed significant hypoglycemic activity. Glibenclamide (oral hypoglycemic agent, 25 mg/kg, p.o.) has been used as standard. Key words: Stephania glabra, Menispermaceae, hydroxypalmatine, alloxan, glibenclamide, hypoglycemic activity DOI:10.3329/jom.v11i1.4262 J Medicine 2010: 11: 17-19